Curimatopsis maculosa, a new species from the Rio Tapajos, Amazon basin, Brazil (Teleostei: Curimatidae) - Melo, Bruno F. [UNESP]; Vari, Richard P.; Oliveira, Claudio [UNESP] (Verlag Dr Friedrich Pfeil, 2016)
Curimatopsis maculosa, new species, is described from the middle portion of the Rio Tapajos, a southern tributary of the Rio Amazonas. It differs from all congeners by the presence of a pointed small, rotund spot of dark pigmentation overlying the posterior most midlateral scales and the base of the middle caudal-fin rays together with morphometric and meristic features. It shares two synapomorphies with C. macrolepis and C. microlepis, related to the postorbital portion of head and an upturned mouth, and is hypothesized to be most closely related to those species.